On liberty - Mill, John Stuart, 1806-1873 (Andrews UK, 2011)
This book is a philosophical work by British philosopher John Stuart Mill. It was a radical work to the Victorian readers of the time, as it supported individuals' moral and economic freedom from the state. This edition has been specially formatted by Andrews UK for today's e-reading devices, and features an easy-to-navigate table of contents.